A influência da cultura organizacional nos conflitos de uma empresa familiar: um estuda na rádio “y” de Rivera - Uruguai - Grau, María Eugenia Viera (2017)
The present research has as general objective to identify the influence of the organizational culture in the conflicts of Radio Y of the city of Rivera - Uruguay, a family business. More specifically, the aim was to characterize radio Y as a family business, to know the organizational culture of radio Y and to verify the most frequent conflicts in the family business studied. In methodological terms, a descriptive, qualitative approach was carried out. The instrument used in the data collection was the semi-structured interview. As a method of data analysis, interpretative analysis was used. It was possible to verify that there are organizational conflicts that affect family relationships, just as there are family conflicts that end up affecting the operation of the company. Many of the conflicts are due to lack of good communication regarding the execution of daily tasks, as well as lack of organization regarding the delegation of roles or roles within the company. It was found that both the owner and the members of the family that make up Radio Y are aware of being the cause of many of the existing conflicts, but did not express a clear or short-term solution to change this conflicting reality that affects the organization